Lipase-catalyzed regioselective preparation of fatty acid esters of hydrocortisone - Quintana, Paula Gabriela (2009)
A series of fatty acid derivatives of hydrocortisone has been prepared by an enzymatic methodology. Nine 21-monoacyl products and one 3,11,17-triacetyl derivative, nine of them novel compounds, were obtained in a highly regioselective way through lipase-catalyzed esterification, transesterification and alcoholysis reactions. The influence of various reaction parameters such as acylating agent: substrate ratio, enzyme: substrate ratio, solvent, temperature and nature of acylating agent and alcohol was evaluated. Among the tested lipases, Candida antarctica lipase appeared to be the most appropriate and showed a high efficient behavior especially in a one-pot transesterification. The advantages presented by this methodology, such as mild reaction conditions and low environmental impact, make the biocatalysis a convenient way to prepare acyl derivatives of hydrocortisone. These lipophilic compounds are potential products in the pharmaceutical industry.